Gynecologic Cancer InterGroup (GCIG) Consensus Review for Clear Cell Carcinoma of the Ovary. (1st November 2014) - Okamoto, Aikou; Glasspool, Rosalind M.; Mabuchi, Seiji; Matsumura, Noriomi; Nomura, Hiroyuki; Itamochi, Hiroaki; Takano, Masashi; Takano, Tadao; Susumu, Nobuyuki; Aoki, Daisuke; Konishi, Ikuo; Covens, Alan; et al.
Abstract : Abstract: Clear cell carcinoma of the ovary (CCC) is a histologic subtype of epithelial ovarian cancer with a distinct clinical behavior. There are marked geographic differences in the prevalence of CCC. The CCC is more likely to be detected at an early stage than high-grade serous cancers, and when confined within the ovary, the prognosis is good. However, advanced disease is associated with a very poor prognosis and resistance to standard treatment. Cytoreductive surgery should be performed for patients with stage II, III, or IV disease. An international phase III study to compare irinotecan/cisplatin and paclitaxel/carboplatin as adjuvant chemotherapy for stage IIV CCC has completed enrollment (GCIG/JGOG3017). Considering the frequent PIK3CA mutation in CCC, dual inhibitors targeting PI3K, AKT in the mTOR pathway, are promising. Performing these trials and generating the evidence will require considerable international collaboration.